The effect of ultrasound-guided erector spinae plane block combined with dexmedetomidine for postoperative pain management in lumbar spine surgery: A case-based discussion - Coppolino, Francesco; Sansone, Pasquale; Porfidia, Carmela; Passavanti, Maria Beatrice; Pota, Vincenzo; Giaccari, Luca Gregorio; Aurilio, Caterina; Pace, Maria Caterina (Frontiers in Anesthesiology, 2023)
Background: Ultrasound-guided erector spinae plane block (US-ESPB) can be valid resources of simple and safe execution in a multimodal approach to postoperative pain management in lumbar spine surgery. It has been shown that the use of multimodal anesthesia reduces the use of intraoperative and postoperative opioids, and also improves analgesia. A growing body of evidence supports that the adjuvant use of dexmedetomidine in locoregional anesthesia significantly prolongs the analgesia and potentiates the effect of the block, without clinically significant side effects. Case presentation: A series of six consecutive patients received bilateral ultrasound-guided erector spinae plane blocks (US-ESPB) with local anesthetics and dexmedetomidine as part of a multimodal analgesic therapy after lumbar spine surgery. Treatment adequacy was evaluated using NRS and OBAS scores; the observed results were overalll satisfactory for all patients. Conclusion: Bilateral US-ESPB appears to be helpful in providing adequate postoperative analgesia after lumbar spine surgery. It’s simple and safe, and so it is unique when compared to other blockages. The addition of Dexmedetomidine as an adjuvant seems to improve analgesic effectiveness and durability.